Evaluation of the multimodal DELTA therapy for adolescents with substance use disorders: an exploratory pilot trial - Basedow, Lukas A.; Kuitunen-Paul, Soeren; Wiedmann, Melina F.; Roessner, Veit; Golub, Yulia (Frontiers in Psychiatry, 2024)
Background: In order to address the lack of manualized treatment programs for adolescents with substance use disorders (SUDs), we developed a manualized group intervention (DELTA). DELTA focusses on substance use reduction and abstinence as well as alleviation of SUD symptoms via additional modules for co-occurring disorders. The goal of this exploratory trial was to assess if DELTA can be conducted in adolescent SUD patients and if participation is related to reductions in substance use, SUD-related problems, and further psychopathologies.We recruited adolescents at a psychiatric outpatient unit, which were then allocated to either DELTA intervention group (N = 85) or to a waiting-list control group (WL, N = 61) based on parental decision to start a therapy or not. Self-report measures were used as primary outcomes (substance use via interview, use-related problems via DUDIT -Drug Use Disorder Identification Test) and secondary outcomes (psychopathologies via YSR -Youth Self Report). T-tests and Pearson correlations were used to analyze between-group differences across time.Results: On average, participants attended M = 7.7 (SD = 5.1) of the 16 sessions. Substance use and use-related problems regarding all substances but nicotine was decreased after the intervention, with small to medium not significant effects in favor of DELTA. Self-reported psychopathologies were also reduced at follow-up, with non-significant advantages for DELTA.Conclusions: DELTA showed small effects on SUD-related and depression-related variables. However, the interpretation is limited by the small sample size. Nonetheless, the DELTA intervention is viable in SUD outpatient treatment and will be further evaluated.2 This is a provisional file, not the final typeset article Trial registration: The study was registered at clinicaltrials.gov under NCT03444974. Registered February, 26th 2018, (https://clinicaltrials.gov/ct2/show/NCT03444974)..